2018
DOI: 10.1002/jez.b.22791
|View full text |Cite
|
Sign up to set email alerts
|

Where is, in 2017, the evo in evo‐devo (evolutionary developmental biology)?

Abstract: After the inaugural Pan-American-Evo-Devo meeting (2015, Berkeley), I showed how major concerns about evo-devo (Evolutionary Developmental Biology) research were demonstrated by a simple, non-biased quantitative analysis of the titles/abstracts of that meeting's talks. Here, I apply the same methodology to the titles/abstracts of the recent Pan-American-Evo-Devo meeting (2017, Calgary). The aim is to evaluate if the concerns raised by me in that paper and by other authors have been addressed and/or if there ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…(1) makes explicit the fact that often novelties are not absolute discontinuities but can be built on previously existing parts, (2) indicates that they are a phenomenon that affects the evolution of certain lineages without implying that all derived characters are in fact novelties, and (3) requires some kind of ecological function to eventually be coupled with the novelty, although it does not imply a necessary link between novelties and adaptive radiations." (Pigliucci, 2008) According to Pigliucci, the prospects of an explanation of evolutionary novelties by evo-devo are meagre, because evo-devo has been focused much more on development than on evolution and is concentrated on the molecular underpinnings of quantitative traits rather than on the underpinnings of the formation of complex new traits This trend is confirmed by recent quantitative analysis of research in the field (Diogo, 2016(Diogo, , 2018.…”
Section: Circularity or Infinite Regressmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) makes explicit the fact that often novelties are not absolute discontinuities but can be built on previously existing parts, (2) indicates that they are a phenomenon that affects the evolution of certain lineages without implying that all derived characters are in fact novelties, and (3) requires some kind of ecological function to eventually be coupled with the novelty, although it does not imply a necessary link between novelties and adaptive radiations." (Pigliucci, 2008) According to Pigliucci, the prospects of an explanation of evolutionary novelties by evo-devo are meagre, because evo-devo has been focused much more on development than on evolution and is concentrated on the molecular underpinnings of quantitative traits rather than on the underpinnings of the formation of complex new traits This trend is confirmed by recent quantitative analysis of research in the field (Diogo, 2016(Diogo, , 2018.…”
Section: Circularity or Infinite Regressmentioning
confidence: 99%
“…As a synthesis of disciplines, evo-devo contains many research programs. However, empirical research in evo-devo is dominated by the study of development based on developmental genetic concepts, methods and tools; considerations of higher level of organisation and of evolutionary problems are undertaken only by a small part of evo-devo scientists (Diogo, 2016(Diogo, , 2018. At the same time, evo-devo can refer to a theoretical construct that is opposed by some scientists and philosophers to the still dominant paradigm in evolutionary 1 Different meanings have been given to the distinction between novelty and innovation.…”
Section: General Introductionmentioning
confidence: 99%
“…This presentation was remarkable because Lynch not only quantitatively characterized the adaptive trait—variation in physiological sensitivity to DNA damage—but also showed that it evolved via an unusual mechanism, for example, a refunctionalized pseudogene that by chance acquired a p53‐responsive cis‐regulatory element. Rui Diogo (Howard) presented a poster, “Evolutionary developmental pathology: a new field of evo‐devo combining anatomy, anthropology, development, genetics, and pathology,” putting into practice some of the ideas articulated in his commentary advocating for more integrative evodevo and for studies linking evodevo with evolutionary medicine (Diogo, ).…”
Section: Evolutionary Medicinementioning
confidence: 99%
“…Diogo and others remarked that the first PASEDB meeting reflected a bias in the field toward molecular/genetic developmental studies, to the detriment of evolution, behavior, ecology (Diogo, ). The second meeting had a more organismal feel but still showed a bias toward developmental biology and genetics based on a quantitative analysis of the titles and abstracts (Diogo, ). This is perhaps unsurprising, given the advent of new technologies like CRISPR that have allowed researchers to probe the function of genes in non‐model species, a feat that was much more difficult only 5–6 years ago.…”
Section: Introductionmentioning
confidence: 99%
“…This argument is antithetical to the way most evolutionary studies are conducted. In fact, it has been argued that there is a dearth of evolutionary analyses within modern Evo‐devo (Diogo, , ). We feel strongly that the synergistic approach of employing experimental model species and comparative analysis of model clades is where the most novel insights will emerge in the coming years.…”
Section: Introductionmentioning
confidence: 99%